Inequality, concentrated disadvantage, and homicide: towards a multi-level theory of economic inequality and crime. Issue 3 (3rd July 2022) - Tuttle, James
ABSTRACT: One of the most consistent findings in the cross-national literature is the association between economic inequality and homicide rates. However, recent research has raised doubts concerning causality. To address some of these concerns, I draw on a (modified) version of Coleman's theory-building model to connect societal-level economic inequality and homicide rates through mechanisms operating at the neighbourhood level. The causal pathway operates through three mechanisms. First, greater economic inequality within society corresponds with higher degrees of spatial segregation by income across neighbourhoods. Second, spatial segregation contributes to concentrated disadvantage and less social integration of the lowest economic stratum, described as (reduced) collective efficacy and social isolation. Finally, more tenuous social integration contributes to higher rates of crime due to weakened social control and cultural/social adaptations to social isolation. This integration of the cross-national and neighbourhood literatures provides new avenues for research on the societal inequality/homicide association.